A study of the efficacy of hyaluronan on post-extraction cases among the walk-in patients of UPCD - Adorable, Maria Angelyn Karla P.; Fonacier, Marian V.; Ermita, Christian Anthony M. (Co-author).; Faustino, Maria Karla T. (Adviser).
Tooth extraction is one of the most common dental procedures that subsequently lead to post-operative discomfort. The study aims to determine the efficacy of hyaluronan (Gengigel®) in reducing healing time and intensity of pain in post-extraction cases among patients in UPCD. Methods and Materials: The 11 participants included in the study underwent a cross-over treatment of hyaluronan and a placebo for their two extraction sites. They were then instructed to determine the healing day and assess pain through a visual analog pain scale, which they recorded in a log diary. Intraoral photographs of their extraction sites were also taken at three different days of the week to observe the rate of soft tissue coaptation of each extraction site. Results: Seven out of the 11 participants subjectively claimed faster healing for hyaluronan, while the remaining four claimed same healing day for both hyaluronan and placebo (p = 0.017). There was a marked difference in wound size reduction for the hyaluronan week for all patients (p = 0.03) measured through the coaptation of the soft tissues using the intraoral photographs. Nine out of the 11 participants reported statistically significant reduction in pain scores during their hyaluronan week. However, there was no significant difference in the mean rate of change in pain scores five minutes and one hour after application of either gel. Conclusion: Hyaluronan appears to improve the healing capacity and consequently reduce the post operative pain experience in simple extraction cases.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Hyaluronic acid - Therapeutic use